Measuring Best Practices for Workplace Safety, Health, and Well-Being: The Workplace Integrated Safety and Health Assessment. Issue 5 (May 2018) - Sorensen, Glorian; Sparer, Emily; Williams, Jessica A.R.; Gundersen, Daniel; Boden, Leslie I.; Dennerlein, Jack T.; Hashimoto, Dean; Katz, Jeffrey N.; McLellan, Deborah L.; Okechukwu, Cassandra A.; Pronk, Nicolaas P.; Revette, Anna; et al.
Abstract : Objective: To present a measure of effective workplace organizational policies, programs, and practices that focuses on working conditions and organizational facilitators of worker safety, health and well-being: the workplace integrated safety and health (WISH) assessment. Methods: Development of this assessment used an iterative process involving a modified Delphi method, extensive literature reviews, and systematic cognitive testing. Results: The assessment measures six core constructs identified as central to best practices for protecting and promoting worker safety, health and well-being: leadership commitment; participation; policies, programs, and practices that foster supportive working conditions; comprehensive and collaborative strategies; adherence to federal and state regulations and ethical norms; and data-driven change. Conclusions: The WISH Assessment holds promise as a tool that may inform organizational priority setting and guide research around causal pathways influencing implementation and outcomes related to these approaches. Abstract : Supplemental Digital Content is available in the text